Production of lipid mediators in mastitic milk of cow. (30th May 2019) - Hayashi, Akane; Fujii, Shota; Nakamura, Tatsuro; Kobayashi, Koji; Sakatani, Miki; Endo, Maiko; Takahashi, Tomotsugu; Murata, Takahisa
Abstract: Bovine mastitis is one of the most prevalent and costly diseases in the dairy industry. Lipid mediators are signaling molecules which coordinately and intricately modulate inflammation. They are produced from polyunsaturated fatty acids (PUFAs) in the cellular membrane via several enzymes including cyclooxygenase (COX) and lipoxygenase (LOX). In the present study, we performed comprehensive analysis of lipid production in milk obtained from clinical or subclinical mastitic cows using liquid chromatography/mass spectrometry. We detected 26, 24, and 40 kinds of lipid constantly in healthy, subclinical, and clinical mastitic milk, respectively. In clinical mastitic milk, the amount of a major n‐6 PUFA, arachidonic acid (AA), tended to increase, whereas amounts of major n‐3 PUFAs, eicosapentaenoic acid and docosahexaenoic acid, tended to decrease. The amounts of several AA‐derived lipids including COX‐catalyzed prostaglandin (PG) D2 and PGE2, and LOX‐catalyzed leukotriene (LT) B4 were increased in clinical mastitic milk. Although subclinical mastitic milk represented similar trend of lipid production to healthy milk, amounts of several lipids such as LTD4, 14, 15‐dihydroxyeicosatrienoic acid, and 14‐epoxyeicosatrienoic acid changed. These findings would be helpful for better understanding of mastitis pathology and give us some insights to develop a new diagnostic and therapeutic strategy.